Importance of nasal septal cartilage perichondrium for septum strength mechanics: a cadaveric study - Tekke, Nihal Seden; Alkan, Zeynep; Yigit, Ozgur; Bekem, Aylin; Unal, Ahmet; Sahin, Feyzi; Balikci, Hasan Huseyin; Acioglu, Engin; Durna, Yusuf Muhammed (INT RHINOLOGIC SOC, 2014)
Objective: This study aimed to investigate the biomechanical qualities of the perichondrium and cartilage, and to determine the strength of the septal cartilage against bending forces. Study Design: This paper describes an experimental cadaver study. Materials and methods: The nasal septal cartilages of 14 fresh cadavers (8 hours postmortem) were excised from the cadavers and cut into two strips: one with the perichondrium (group A) and one without perichondrium (group B). A bending test was then performed on the strips. Results: The deflection of group A strips was larger than the deflection of group B strips. Flexural strength was also larger in group A strips compared to group B strips. The average modulus of elasticity was 122% higher in group A compared to group B. All conducted tests revealed statistically significant differences between groups. Conclusion: This study objectively shows that the perichondrium provides the cartilage with a 25% bending strength.
Keywords: septal cartilage; perichondrium; biomechanics; bending test; Otorhinolaryngology